INTEGRATION OF SCIENCE MATERIAL IN COLLEGE CURRICULUM: IMPACT ON PGAUD STUDENTS' MOTIVATION AND LEARNING INTEREST - Murniasih S, Ni Putu (STAH Dharma Sentana Sulawesi Tengah, 2025)
This study analyzes how the motivation, interest, and readiness of Early Childhood Teacher Education (PGAUD) students are affected by courses that integrate science materials into the college curriculum. This study conducted a qualitative case study with 17 PGAUD students who took courses that integrated science materials. To ensure the validity of the results, data triangulation techniques were used to collect data; these methods included participant observation, in-depth interviews, and observation sheets. The results showed that science materials enhanced the curriculum. The experiment-based approach made science more interesting and easier to understand, from 82% of students (14 of 17), and because the learning was more practical and experiential, from 88% of students (15 of 17). 76% of students (13 of 17) said they were more prepared to apply science learning after class. However, 30% of students (5 of 17) said they faced problems in learning science, such as lack of laboratory equipment and difficulty understanding more abstract concepts. Based on these findings, the PGAUD curriculum should focus more on experiment-based learning and provide sufficient practical resources to improve the quality of science teaching in early childhood education.